2018
DOI: 10.1042/bsr20171132
|View full text |Cite
|
Sign up to set email alerts
|

Zhenbao pill protects against acute spinal cord injury via miR-146a-5p regulating the expression of GPR17

Abstract: The aim of the present study was to observe the effect of zhenbao pill on the motor function of acute spinal cord injury (ASCI) rats and the molecular mechanisms involving miR-146a-5p and G-protein-coupled receptor 17 (GPR17). ASCI rat model was established by modified Allen method, and then the rats were divided into three groups. SH-SY5Y cells were cultured overnight in hypoxia condition and transfected with miR-146a-5p mimic or miR-146a-5p inhibitor. The hind limb motor function of the rats was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Unfortunately, as was proven many times in the past, ideal and universal control gene(s), which is/are stably expressed across all cell types or under different conditions, do not exist [5,9,26]. Therefore, it is recommended that the combination of several validated RGs is employed to minimize the inherent variation in their expression [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, as was proven many times in the past, ideal and universal control gene(s), which is/are stably expressed across all cell types or under different conditions, do not exist [5,9,26]. Therefore, it is recommended that the combination of several validated RGs is employed to minimize the inherent variation in their expression [19].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies dealing with gene expression during postnatal development and after spinal cord injury circumvent RG validation. Thus, the authors often rely on the routinely used housekeeping genes, mostly e.g., Gapdh [9,10], β-actin [11,12], or 18S rRNA [13,14], without testing and validating its stable expression under particular experimental conditions. To our knowledge, we are not aware of a serious survey and validation of stably expressed RGs in the rat spinal cord across postnatal development or after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, Zhenbao Pill could repair the damaged neurones, promote microcirculation, and remove oxygen free radicals [ 8 , 9 ], suggesting the potential application of Zhenbao Pill in treating SCI patients. Indeed, Zhenbao Pill has been shown to protect SCI rats from further damage [ 10 , 11 ], with improved BBB score. Consistent with this finding, in the present study, we also found that the BBB score was significantly lower in SCI group compared with sham group, which was dramatically reversed by Zhenbao Pill.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that Zhenbao Pill had the function of repairing damaged neurones, promoting microcirculation, and removing oxygen free radicals [ 8 , 9 ]. Our previous research has found that Zhenbao Pill had a protective effect on the nerves of SCI rats [ 10 ]. We also found that Zhenbao Pill improved the performance of SCI rats in the Basso, Beattie, and Bresnahan (BBB) score and reduced the proportion of Treg cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia treatment was performed in AGE1.HN and PC12 cell lines for simulating SCI in vitro, as previously reported [14,15]. Oxygenglucose deprivation (OGD) was performed upon the above cells for hypoxia treatment in accordance with a previous study [16].…”
Section: Western Blottingmentioning
confidence: 99%